High-speed rail and local economic development: An analysis based on innovations, local and national spaces and local actors' strategies - Marie Delaplace (European Regional Science Association (ERSA), 2010)
There are a lot of High-Speed Rail projects in a lot of countries (Belgium, Brazil, China, France, Germany, Portugal, USA, etc.). In 2009, 13469 km of High-Speed Lines are under construction and 17579 km are planned all around the world by 2025 (Barroni I, 2009). In the past and in some territories, some local economic dynamics linked to this kind of infrastructure have emerged. The aim of this communication is to present the conditions in which a HSR contributes to a local economic development. By using service innovation theories (Gallouj, 2003, Gallouj et Weinstein 1997), we propose a theoretical analysis of the arrival of a High-Speed Rail Service in a territory as a set of innovations (ameliorative innovation, incremental innovation, relational innovation). But these innovations must be appropriated. This appropriation that modifies the actions of actors can be individual: an actor will integrate it in its strategy by individually offering innovations of product/service. But it can be collective. From this collective appropriation can emerge complementary innovations of products/services based on relational innovations in the territory. They can give birth to the definition of a project of territory which will lead the actors to innovate in the relationships with the other actors of the territory and to create a new organization with a specific goal. In such a case, the private and public actors, beyond their individual interest, are coordinating their actions in order to promote a development of the territory which is linked to their own development by producing coherent and collective policies likely to valorize resources (economic, cultural, human and land) of the territory . Using Schumpeterian analysis (Schumpeter, 1939), we argue that the emergence of several relational innovations between private and public actors associated with innovations of products/services, that we consider as a cluster of services innovations are the central elements in the link between HSRS and local economic development. Thus if the HSRS opens up potentialities, their fulfillment depends on the way playing agents, likely to profit from it, i.e. how they will integrate the various innovations in their behaviors, and eventually produce new ones.
Keywords: 330